2011
DOI: 10.1515/hf.2011.084
|View full text |Cite
|
Sign up to set email alerts
|

Fungal degradation of bamboo samples

Abstract: The degradation of several Asian bamboo species by white-, brown-, and soft-rot fungi was investigated under laboratory conditions by means of different test methods. Severe deterioration was caused by all three fungi types. The bamboo species differed in durability. Samples from 6 months young culms decayed more than older ones. There were no significant differences between 1-and 3-year-old culms. Samples taken from the culm top were more vulnerable to decay than those from the bottom. Wet bamboo samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Some variation between the sites was observed, i.e., from moderately to non-durable, that might be explained by the prior location of the lamellae in the culm. Numerous studies on the decay and natural durability of bamboo species have been conducted (Liese 1985;Leithoff and Peek 2001;Schmidt et al 2011) and the durability of Bambusa vulgaris grown in Indonesia reported (Suprapti 2010). Applying the standard EN 113, Wei et al (2013) classified five bamboo species in durability class 2 by using four C. puteana and two G. trabeum strains; the white-rot fungus T. versicolor yielded durability classes 2 to 4 and two soft-rot fungi showed classes 2 to 3.…”
Section: Durability and Treatability Of Bamboomentioning
confidence: 99%
“…Some variation between the sites was observed, i.e., from moderately to non-durable, that might be explained by the prior location of the lamellae in the culm. Numerous studies on the decay and natural durability of bamboo species have been conducted (Liese 1985;Leithoff and Peek 2001;Schmidt et al 2011) and the durability of Bambusa vulgaris grown in Indonesia reported (Suprapti 2010). Applying the standard EN 113, Wei et al (2013) classified five bamboo species in durability class 2 by using four C. puteana and two G. trabeum strains; the white-rot fungus T. versicolor yielded durability classes 2 to 4 and two soft-rot fungi showed classes 2 to 3.…”
Section: Durability and Treatability Of Bamboomentioning
confidence: 99%
“…Therefore, to explore antimicrobial potential of natural plants scientists have carried out extensive research on extracts and oils of various plant products. In present study Neem oil has been tested against various fungi including white rot, brown rot, soft rot and sap stain which cause decay in wood as well as bamboo (Sharia et al 2012;Kumar et al 2013;Hyde et al 2001;Schmidt et al 2011). Neem oil is known to possess antimicrobial propertied and has been widely studied for its potential against fungi (Khetarpal 2010).…”
Section: Introductionmentioning
confidence: 98%
“…However, bamboo has a low natural durability and is attacked by fungi during storage, transport, processing and final use (Liese and Kumar 2003). There are several reports on its degradation by fungi (Liese 1959(Liese , 1985Abdurachim 1964, Mohanan 1997, Kim et al 2011, Suprapti 2010, Ma et al 2010, Schmidt et al 2011. The behaviour of bamboo against decay fungi is an important parameter in bamboo establishment and use.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations revealed that bamboo degradation is due to white and soft rot fungi, whereas brown-rot species were less aggressive. Among the investigated fungi, Coniophora puteana and Schizophyllum commune varied with respect to the test method used: Low maximum mass loss was measured on agar under pure culture condition, whereas considerable degradation occurred in the `fungus cellar test´ where the samples are placed in large metal containers on unsterile garden soil with different moisture accessibility (Schmidt et al 2011). However, C. puteana and S. commune differed in decay activity: C. puteana produced maximum mass loss at low moisture content of 57%, whereas decay by S. commune was highest at 182% moisture content (Schmidt et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation